Optimum Sowing Date And Fertilizer Management For Durum Wheat Genotype DWK 38 In Mid-Hills Condition - Chaulagain, Bhimsen; Bhattarai, Rajendra Kumar; Gyawaly, Pankaj (Agronomy Journal of Nepal, 2021)
Durum wheat is relatively new crop for Nepal and research on durum wheat were carried out only by Agriculture Botany Division of Nepal Agricultural Research Council (NARC). To find the optimum sowing time and fertilizer dose for mid-hills conditions of Nepal, an experiment was carried out in 2017/18 and 2018/19 at Agronomy Division Experimental farm in Khumlatar at an altitude of 1360 masl. The experimental design was factorial randomised complete block design. There were 3 fertilizer level and 4 sowing date constituting 12 treatment combinations. From the combined analysis over years, we found that plant height, days to heading, days to maturity, thousand grain weight and grain yield were found significnat in sowing date whereas number of tillers per square meter, straw yield and harvest index were significant in fertilizer doses. Combined analysis of both years yielded mean grain yield of 5.2 t/ha and thousand grain weight of 48.6 gm respectively. Precipitation during reproductive period (March[1]April) in 2017/18 contributed in higher grain yield than 2018/19. Optimum sowing date of durum wheat for khumaltar condition is no later than 26 November and optimum dose of fertilizer is 125:75:50 N:P2O5:K2O kg/ha.